An economic analysis of land titling in Honduras - Larson, J; Larson, Janelle B. Montaner (1995)
﻿ In 1982 the governments of Honduras and the United States signed a contract that established the Proyecto de Titulación de Tierras, or land titling project. This project was initiated primarily to provide titles to small coffee farmers on State-owned land. Among the expected consequences of the project were increased access to resources, especially credit, for small farmers and increased on-farm investment due to this access to credit and increased security. It was hoped that a greater use of credit and investment would increase farm production and therefore the income and well-being of the farmers involved. In this dissertation, the land titling project is placed within the context of the history of agrarian reform in Honduras. The titling project called for a baseline study and final evaluation. These were carried out in 1983 and 1988, respectively. The author was able to obtain these data and re-interview the same farmers in 1993. These farmers are from two regions, one of which was titled and another which was not. The interviews gathered data on production, credit, use of inputs, investments, income and general socio-economic indicators. These data are used to determine the extent to which the goals of the tiding project have been met. A stochastic frontier production function is used to estimate farm-level technical efficiency. Following this, these technical efficiency scores are regressed on various factors such as education, credit and technical assistance to estimate their possible effects on technical efficiency. Finally, simultaneous equations are used to estimate the relationships among these variables. In general, ten years after the start of the project, the original goals have not been achieved. This analysis found that titling does not affect technical efficiency, access to credit, or the use of inputs. Education and technical assistance are the two factors that are consistently the most significant in meeting the project's stated goals. This analysis suggests that basic education and technical assistance, rather than expensive land titling projects, should be promoted to enhance access to credit, the use of inputs and increased technical efficiency.